FAKTOR PERILAKU ANAK YANG BERHUBUNGAN DENGAN PENYAKIT KECACINGAN PADA ANAK DI DESA PAHOKNG KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - Lidia, Marselina; Ridha, Abduh; Trisnawati, Elly (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
wormy worm infection or disease has always been a disease that threatens the health of children, intestinal worm infections do not cause obvious symptoms so that less attention, but result in digestive disorders, circulatory, anemia, allergies, obstruction, irritation and intestinal perforation. This disease if infected organ weight will strike the heart, lung, pancreas, appendix even to the brain. Helminthiases attacking at primary school age children, especially those living in areas where the parasite is transmitted actively. Pahokng village had the highest prevalence of worm infection in children of primary school age are 75.9% in 2012, in 2013 increased to 77%. This study aims to identify factors associated with the child's behavior de- worming children in the village PahokngMempawah Hulu subdistrict Porcupine District.This study uses a case control design. Research as many as 41 cases and 41 kontrolorang taken by purposive sampling technique using chi-square test with 95% confidence level.The results showed that there is a relationship between the nail biting habit (p value = 0.039, PR = 2.958, 95% CI = 1.154 to 7.556), the habit of playing on the ground barefoot (p value = 0.043, PR = 2.95, CI 95 % = .101-.870), a habit of playing in the muddy ground (p value = 0.043, PR = 3.365, 95% CI = 1.150 to 9.852), kebiasaa BAB family (p value = 0.039, PR = 3.733, 95% CI = 1.198 -11.633) with the incidence of intestinal worms in children of primary school. Variables are not related, the habit of eating raw vegetables without washing it first (p value = 1.000)It is suggested to parents to forbid children to bite your nails, cut nails routine children, providing slippers for children and do not defecate in any place. Keywords: incidence of worm infection, child's behavior and attention of parents.